2017
DOI: 10.3174/ajnr.a5233
|View full text |Cite
|
Sign up to set email alerts
|

Acute Basilar Artery Occlusion: Differences in Characteristics and Outcomes after Endovascular Therapy between Patients with and without Underlying Severe Atherosclerotic Stenosis

Abstract: Underlying intracranial atherosclerotic stenosis was not uncommon in patients with acute basilar artery occlusion. The occlusion segment of the basilar artery and the presence or absence of bilateral thalamic infarction on a pretreatment DWI might be helpful for predicting underlying intracranial atherosclerotic stenosis in patients with acute basilar artery occlusion. Patients with and without underlying intracranial atherosclerotic stenosis who underwent endovascular therapy had similar outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 20 publications
4
72
2
Order By: Relevance
“…Basilar atheroma has been suggested as a potentially important factor to BAO outcome, as difficulty of EVT may increase when intracranial atherosclerotic disease is involved . This study has shown direct relationships between basilar atheroma and increased rates of intra‐procedural complications and longer EVT times, both of which themselves correlate with lower revascularization and higher mortality.…”
Section: Discussionmentioning
confidence: 60%
“…Basilar atheroma has been suggested as a potentially important factor to BAO outcome, as difficulty of EVT may increase when intracranial atherosclerotic disease is involved . This study has shown direct relationships between basilar atheroma and increased rates of intra‐procedural complications and longer EVT times, both of which themselves correlate with lower revascularization and higher mortality.…”
Section: Discussionmentioning
confidence: 60%
“…This finding suggests that emergent dilatation of the basilar artery should be avoided in the acute reperfusion BAO procedure. On the contrary, although the population was different, a similar mortality rate was observed in a retrospective study of 62 Chinese patients with and without underlying intracranial atherosclerotic stenosis treated with stent retriever thrombectomy [25]. Further studies are warranted.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, a similar study regarding acute BA occlusion with endovascular treatment found no differences in recanalization rate and outcome between patients with and without underlying ISAT. 27 However, the criterion for an ISAT used in that study was a severe (≥70%) stenosis of BA on the initial diagnostic angiography or on the follow-up angiography after a reperfusion procedure. Therefore, at least transient recanalization of the occluded BA was required to determine an ICAS mechanism, unless the patient was diagnosed as a severe BA stenosis previously to the stroke event.…”
Section: Discussionmentioning
confidence: 96%